2009
DOI: 10.7863/jum.2009.28.11.1493
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Alzheimer Disease Have Altered Transmitral Flow

Abstract: Objective. There is considerable epidemiologic evidence that Alzheimer disease (AD) is linked to cardiovascular risk factors and associated with an increased risk of symptomatic left ventricular (LV) dysfunction. Formation of a vortex alongside a diastolic jet signifies an efficient blood transport mechanism. The vortex formation time (VFT) is an index of optimal conditions for vortex formation. We hypothesized that AD and its associated cardiovascular risk factors impair diastolic transmitral flow efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 53 publications
2
12
1
Order By: Relevance
“…However, our findings were associated with statistically significant impairment of diastolic parameters in the AD group when compared with the ND group. Similar to our findings, Belohlavek et al19 found that patients with AD have altered mitral inflow parameters and vortex formation time. However, they did not evaluate for the more sensitive tissue Doppler parameters for diastolic functions that we observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, our findings were associated with statistically significant impairment of diastolic parameters in the AD group when compared with the ND group. Similar to our findings, Belohlavek et al19 found that patients with AD have altered mitral inflow parameters and vortex formation time. However, they did not evaluate for the more sensitive tissue Doppler parameters for diastolic functions that we observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Hypertension, diabetes, stroke, and atherosclerosis have been shown to increase AD risk 7,24,25. During the aging process, heart, arteries, and brain suffer the continuous cumulative consequences of hemodynamic and mechanical stresses;19,2628 further, the myocardium undergoes structural changes including interstitial fibrosis and cellular disarray, which affects the diastolic functions negatively as a result of aging 2931…”
Section: Discussionmentioning
confidence: 99%
“…Impaired left ventricular diastolic filling efficiency, as assessed by vortex formation time and detected by echocardiography, was significantly decreased in AD patients compared with NDC subjects 48. These findings suggest that intraventricular blood conveyance is suboptimal in AD and that left ventricular diastolic dysfunction is related to cognitive deficits 48. Decreased pulse pressure could be part of the pathogenesis of AD and/or synergistically contribute to the development of this neurodegeneration, given that oligemic and hypoxic changes in the AD brain may also result from destruction of the vasoactive brain centers that regulate cerebral perfusion 49.…”
Section: Discussionmentioning
confidence: 87%
“…Subclinical dysfunctional heart disease may result in decreased cardiac output that may lead to lower pulse pressure in AD patients. Impaired left ventricular diastolic filling efficiency, as assessed by vortex formation time and detected by echocardiography, was significantly decreased in AD patients compared with NDC subjects 48. These findings suggest that intraventricular blood conveyance is suboptimal in AD and that left ventricular diastolic dysfunction is related to cognitive deficits 48.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous cross-sectional and longitudinal studies, using various imaging and ultrasound techniques, have shown that in AD there is an statistically significant reduction in total and regional cerebral blood flow when compared to age matched controls [24-32]. Echocardiographic investigations demonstrated that AD subjects exhibited a statistically significant diastolic dysfunction revealed by increased transmitral vortex formation time [33]. Likewise, duplex Doppler carotid ultrasound showed a consistent and significant decrease in diastolic flow along the path of the carotid artery in AD patients, suggesting a loss of arterial elastic capacity [34].…”
Section: The Role Of Cardiovascular Disease Diabetes and Head Traumamentioning
confidence: 99%